2011
DOI: 10.1042/bst0391191
|View full text |Cite
|
Sign up to set email alerts
|

Melanosomes on the move: a model to understand organelle dynamics

Abstract: Advances in live-cell microscopy have revealed the extraordinarily dynamic nature of intracellular organelles. Moreover, movement appears to be critical in establishing and maintaining intracellular organization and organellar and cellular function. Motility is regulated by the activity of organelle-associated motor proteins, kinesins, dyneins and myosins, which move cargo along polar MT (microtubule) and actin tracks. However, in most instances, the motors that move specific organelles remain mysterious. Over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 61 publications
(67 reference statements)
2
81
0
1
Order By: Relevance
“…30 Its constitutive association with the platelet granule surface might play a role in anchorage of the granules to F-actin network to allow positioning within the mature MK. F-actin networks indeed provide the scaffold for the anchorage and positioning of secretory granules, 20,31,32 and F-actin-disrupting agents in melanocytes have for instance been shown to result in the formation of melanosome aggregates. [33][34][35] We observed here that myosin deficiency modestly but significantly impairs organelle motility within MKs, in terms of mean displacement ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Its constitutive association with the platelet granule surface might play a role in anchorage of the granules to F-actin network to allow positioning within the mature MK. F-actin networks indeed provide the scaffold for the anchorage and positioning of secretory granules, 20,31,32 and F-actin-disrupting agents in melanocytes have for instance been shown to result in the formation of melanosome aggregates. [33][34][35] We observed here that myosin deficiency modestly but significantly impairs organelle motility within MKs, in terms of mean displacement ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…16 Actin filaments serve as "rails" for the myosin-based traveling of organelles, [16][17][18] and as a support for their location and distribution. [19][20][21] We therefore investigated whether the F-actin cytoskeleton was affected by the absence of myosin. Progenitor cells from bone marrow were cultured for 4 days and allowed to adhere to a fibronectin-coated surface.…”
Section: Absence Of Myosin Iia Impairs F-actin Organizationmentioning
confidence: 99%
“…However, not much is known about the mechanism of microtubulebased transport in melanocytes, including the contributions of the microtubule-associated motors to the melanosome transport (5,6,(8)(9)(10). In contrast, the actin-based transport of melanosomes has been characterized in greater detail.…”
mentioning
confidence: 99%
“…Interestingly, there is evidence of some functional redundancy between Rab3 and its closest homologues, Rab27A and Rab27B, which are involved in the delivery of vesicles near the exocytic site (Fukuda, 2008;Gomi, et al, 2007;Ostrowski, et al, 2010). Studies of melanosome dynamics have indicated that Rab27A has a role in vesicular recruitment and this is mediated by its interaction with a specific effector called Melanophilin, which in turn binds an actin motor protein, MyosinVa (Hume & Seabra, 2011;Seabra & Coudrier, 2004). There appears to be a further functional divergence of Rabs, where Rab27A and Rab27B control different steps of the secretion pathway (Ostrowski, et al, 2010).…”
Section: Rab Gtpases and Vesicular Tetheringmentioning
confidence: 99%